Islamic-Informed Spiritual-Empathic Listening Support for Postpartum Trauma: A Rapid Evidence Review - Fitriana Fitriana; Yudhia Fratidina; Feri Kameliawati; Rahayu Sri Astutik (Poltekkes Kemenkes Palu, 2026)
Background: A worldwide health concern is postnatal psychological discomfort, which includes symptoms of anxiety, and despair. Although listening-based therapies have become popular as flexible, low-cost ways to treat maternal mental health, there is currently little data on their efficacy and cultural fit. With an emphasis on Islamic-informed approaches, this study sought to compile the most recent data on the efficacy, viability, and cultural significance of listening services in enhancing maternal psychological outcomes. Methods: A Rapid Evidence Review (RER) was conducted following PRISMA 2020 guidelines. Twelve empirical studies published between 2018 and May 2025 were included (4 randomized controlled trials, 3 quasi-experimental studies, 3 observational studies, 1 qualitative, and 1 mixed-method design). Results: Ten of the twelve studies (83%) reported statistically significant reductions in maternal psychological distress. Randomized controlled trials demonstrated measurable decreases in EPDS, PCL-5, and DASS-21 scores following structured midwife-led debriefing or counseling sessions. Several interventions showed significant reductions in postpartum anxiety and PTSD symptoms after brief (1–4 session) models. Faith-integrated listening approaches in Muslim-majority settings enhanced spiritual resilience, emotional validation, and cultural acceptability. Digital and telehealth modalities improved accessibility, particularly during the COVID-19 pandemic, although higher attrition rates and short follow-up durations were frequently noted. Conclusion: Postnatal listening services are an efficient and affordable way to improve the psychological well-being of mothers when paired with treatment that is sensitive to cultural and spiritual differences. Future studies and clinical applications should place a high priority on formalizing Islamic informed listening frameworks in midwifery practice in Muslim communities.